1999
DOI: 10.1203/00006450-199908000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Cortisol-Cortisone Shuttle in Children Born with Intrauterine Growth Retardation

Abstract: We evaluated the involvement of a possible dysfunction of 11beta-hydroxysteroid dehydrogenase type 2 (11beta-HSD2) in the fetal growth retardation and poor growth rates of children born with intrauterine growth retardation (IUGR). Children with IUGR have a nephron deficit and are also at risk of developing cardiovascular diseases, high blood pressure, glucose intolerance, and dyslipidemia later in life. The major site of 11beta-HSD2 production is the kidney and its deficit causes hypertension. We investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
2
25
1
Order By: Relevance
“…Interestingly, the F/E ratios did not differ between the highest F quartiles in the SGA and the AGA group. Thus, our findings were consistent with those of Houang and coworkers (24) in respect of the relationship between serum lipid concentrations and high F/E ratios. However, in our SGA children both high serum F concentration and F/E ratio associated with high total and LDL cholesterol concentration and HOMA-IR index, whereas only high F/E ratio associated with poor catch-up growth.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Interestingly, the F/E ratios did not differ between the highest F quartiles in the SGA and the AGA group. Thus, our findings were consistent with those of Houang and coworkers (24) in respect of the relationship between serum lipid concentrations and high F/E ratios. However, in our SGA children both high serum F concentration and F/E ratio associated with high total and LDL cholesterol concentration and HOMA-IR index, whereas only high F/E ratio associated with poor catch-up growth.…”
Section: Discussionsupporting
confidence: 83%
“…They found that 20% of their IUGR children had high F/E ratios suggesting a possible partial 11␤-HSD2 defect. These IUGR children had significantly higher total cholesterol concentrations, systolic blood pressure, and a tendency toward higher fasting insulin levels than the IUGR children with low F/E ratios and the control children (24). Furthermore, both high F/E ratios (24) and high F levels have been associated with poor catch-up growth (25).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In children, Clark et al reported an association between low birth weight and increased urinary glucocorticoid metabolite excretion (11), while other investigators have not been able to show any association between birth size and circulating cortisol concentrations (12)(13)(14)(15)(16). Thus, according to these studies, the association between fetal growth restriction and later increased glucocorticoid activity in humans is still controversial, at least during childhood.…”
Section: Introductionmentioning
confidence: 99%